2012
DOI: 10.1103/physrevb.85.155412
|View full text |Cite
|
Sign up to set email alerts
|

Transport gap in suspended bilayer graphene at zero magnetic field

Abstract: We report a change of three orders of magnitude in the resistance of a suspended bilayer graphene flake which varies from a few k in the high-carrier-density regime to several M around the charge neutrality point (CNP). The corresponding transport gap is 8 meV at 0.3 K. The sequence of quantum Hall plateaus appearing at filling factor ν = 2 followed by ν = 1 suggests that the observed gap is caused by the symmetry breaking of the lowest Landau level. Investigation of the gap in a tilted magnetic fields indicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
83
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 32 publications
(61 reference statements)
13
83
1
Order By: Relevance
“…Bilayer graphene Bilayer graphene has received a lot of attention, mainly because of the enhanced density of states at zero doping due to parabolically touching bands. Such band structures have been shown to be unstable towards spontaneous symmetry breaking [152] and experimental results have revealed signatures of interaction-driven excitonic states in suspended and undoped graphene bilayers [18,19,20,21,22,23,24,25]. Very recently weak-coupling renormalization group calculations have shown that superconductivity emerges upon doping away from these excitonic states [153].…”
Section: Graphene-like Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilayer graphene Bilayer graphene has received a lot of attention, mainly because of the enhanced density of states at zero doping due to parabolically touching bands. Such band structures have been shown to be unstable towards spontaneous symmetry breaking [152] and experimental results have revealed signatures of interaction-driven excitonic states in suspended and undoped graphene bilayers [18,19,20,21,22,23,24,25]. Very recently weak-coupling renormalization group calculations have shown that superconductivity emerges upon doping away from these excitonic states [153].…”
Section: Graphene-like Systemsmentioning
confidence: 99%
“…[4,5,6,7,8,9,10,11,12,13,14,15,16,17], but most have not been experimentally observed as of yet. One exception is multi-layer graphene systems where there are now experimental reports of an energy gap opening at low temperatures, which has been ascribed to interactions effects [18,19,20,21,22,23,24,25]. Obviously, the possibilities for superconductivity in graphene have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a quantum spin Hall analogue has been predicted at ν = 0 in bilayer graphene if the ground state is a spin ferromagnet 8,9 . Previous studies have demonstrated that the bilayer ν = 0 state is an insulator in a perpendicular magnetic field [10][11][12][13][14][15][16] , though the exact nature of this state has not been identified. Here we present measurements of the ν = 0 state in a dual-gated bilayer graphene device in tilted magnetic field.…”
mentioning
confidence: 99%
“…The application of an in-plane magnetic field and perpendicular electric field allows us to map out a full phase diagram of the ν = 0 state as a function of experimentally tunable parameters. At large in-plane magnetic field we observe a quantum phase transition to a metallic state with conductance of order 4e 2 /h, consistent with predictions for the ferromagnet.Under a strong perpendicular magnetic field, bilayer graphene (BLG) develops a ν = 0 quantum Hall (QH) state at the charge neutrality point (CNP) which displays anomalous insulating behavior [10][11][12][13][14][15][16] . Transport studies in a dual-gated geometry 12-14 indicate that this gapped state results from an interaction-driven spontaneous symmetry breaking in the valley-spin space 17 .…”
mentioning
confidence: 99%
“…4(a), the resistance at the CNP decreases as a function of B /k B T , similar to a recent observation in a suspended BLG sample. 33 This decrease suggests that the gap is suppressed by a magnetic field, = 0 − (B). Assuming a simple Zeeman gap, (B) = 2μ B B , leads to a field dependence shown by the solid lines in Fig.…”
mentioning
confidence: 99%